Medial femoral condyle free flap in combination with paramedian forehead flap for total/subtotal nasal reconstruction: Level of evidence: IV (therapeutic studies): Level of evidence: IV (therapeutic studies). Issue 3 (9th November 2019) - Cherubino, Mario; Stocco, Chiara; Tamborini, Federico; Maggiulli, Francesca; Sallam, Davide; Corno, Martina; Bignami, Maurizio; Battaglia, Paolo; Valdatta, Luigi
Abstract: Background: The nose is a functionally complex organ with also a critical role in aesthetics. For reconstruction of full thickness nasal defects, multiple stages are needed and there is risk for resorption resulting in residual deformity. The aim of this report was to develop and evaluate a new method for full thickness total/subtotal nose reconstruction using the medial femoral condyle free flap (MFCFF) in combination with a paramedian forehead flap. Methods: Between November 2015 and January 2018, eight patients (four males, four females) mean age 52 years (range 40–73 years) undergoing a total/subtotal nasal excision and subsequential reconstruction with MFCFF plus paramedian forehead flap were enrolled. Six cases were squamous cell carcinomas while two were basal cell carcinomas. The MFCFF was stabilized, with the periosteum as inner layer, with plates and a paramedian forehead flap was used as external skin coverage. All patients were evaluated for with postoperative nasal endoscopy and CT scan. A postoperative questionnaire was given 6 months after surgery. Results: The mean MFCFF size was 2–3.8 cm × 2.25–2.5 cm with a mean pedicle length of 6.3 cm (range 4.1–9.4 cm). The postoperative period was uneventful. The mean follow‐up was 16 months, no bone displacement or resorption was observed at the CT scan, no evidence of nasal stenosis occurred. All patients had a satisfying aesthetic evaluation and a good subjective nasal function. Conclusions: In this series, the MFCFF in combination with the paramedian forehead flap appeared to provide a valid subtotal nose reconstruction, allowing for the recreation of all the three nasal layers and maintaining the nose projection and airway patency in the long term.